Relationship Between Study Habits and Academic Performance of Intermediate Students: Evidence from Pakistan - Muhammad Furqan; Muhammad Irfan; Uzair Khan, (Dialogue Social Science Review (DSSR), 2025)
Background: Academic success is influenced not just by intelligence, but by consistent study routines. In Pakistan, students often rely on last-minute study patterns. Aim: To investigate the impact of study habits on academic performance among intermediate students in Dera Ghazi Khan. Methods: A correlational design was used with data from a 20-item questionnaire. Participants included 120 students. Statistical tests included Pearson’s correlation and t-tests. Findings: A significant positive correlation (r = 0.62, p < 0.01) was found between organized study habits and academic performance. Gender differences were statistically insignificant. Conclusion: Regular and disciplined study habits support academic achievement. Institutions and families should promote structured learning routines.